Instrumenty finansowe ochrony gruntów rolnych i leśnych - Bieluk, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Financial instruments belong to basic instruments of agricultural land and forests protection. In the Act on Protection of Agricultural Land and Forests, numerous financial mechanisms aimed at protection of agricultural land against its non-agrarian usage have been established. Among them there are mainly one-time charges and annual payments for the exclusion of land from agricultural production. Solutions suggested in the Act on Protection of Agricultural Land and Forests are not perfect and constitute a source of practical problems. Under the Act, the charge is to be decreased by the amount equal to the value of the ground, calculated on the basis of market prices applied in a given locality in the land trade, on the date of the actual exclusion of the land from production. In practice such a solution rarely obliges a party to the proceedings to make one-time payments. Exemptions from charges and annual payments due to the exclusion of land for the purposes of housing also cause several problems.
Keywords: ochrona gruntów rolnych; wyłączenie ziemi z produkcji rolnej; opłaty jednorazowe; płatności roczne